2004
DOI: 10.1128/jcm.42.2.554-562.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cell-to-Cell Signaling-Deficient Pseudomonas aeruginosa Strains Colonizing Intubated Patients

Abstract: Cell-to-cell signaling involving N-acyl-homoserine lactone compounds termed autoinducers (AIs) is instrumental to virulence factor production and biofilm development by Pseudomonas aeruginosa. In order to determine the importance of cell-to-cell signaling during the colonization of mechanically ventilated patients, we collected 442 P. aeruginosa pulmonary isolates from 13 patients. Phenotypic characterization showed that 81% of these isolates produced the AI-dependent virulence factors elastase, protease, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
63
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 66 publications
10
63
0
Order By: Relevance
“…The result would be a heterogeneous community of QS proficient and QS deficient (cheater) variants. Intriguingly, in the only study to date that has examined the diversity of QS phenotypes of a large number of isolates from individual patients, such mixed populations have been found to exist (37). We suspect that cheating might also provide P. aeruginosa with a selective advantage in natural mixed-species environments in which other bacteria secrete extracellular degradative enzymes that generate the necessary nutrients for growth.…”
Section: Discussionmentioning
confidence: 99%
“…The result would be a heterogeneous community of QS proficient and QS deficient (cheater) variants. Intriguingly, in the only study to date that has examined the diversity of QS phenotypes of a large number of isolates from individual patients, such mixed populations have been found to exist (37). We suspect that cheating might also provide P. aeruginosa with a selective advantage in natural mixed-species environments in which other bacteria secrete extracellular degradative enzymes that generate the necessary nutrients for growth.…”
Section: Discussionmentioning
confidence: 99%
“…For example, P. aeruginosa QS systems have been demonstrated to be important for pathogenesis in multiple animal infection models (325)(326)(327)(328), and AHLs and QS-regulated genes have been demonstrated to be expressed in vivo (329)(330)(331). However, analyses of clinical P. aeruginosa isolates have revealed that lasR, and less frequently rhlR, can be mutated during infection (332)(333)(334)(335)(336). In one study it was demonstrated that a single cystic fibrosis patient acquired at least four independent lasR mutants over an 8-year period (337), suggesting a strong selection pressure in vivo for abolishing LasR-mediated QS during chronic infections.…”
Section: Concernsmentioning
confidence: 99%
“…This growth advantage is at least in part due to increased expression of the regulator CbrB, which regulates various catabolic pathways, suggesting that aberrant expression of other regulators resulting from the loss of LasR function may provide a growth benefit during growth in vivo. Such a growth advantage could explain the emergence of lasR mutant populations during in vivo infection (332)(333)(334)(335)(336)(337).…”
Section: Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus QS plays a predominant role in the regulation of virulence determinants in P. aeruginosa. Surprisingly, however, there are increasing reports that lasR mutants occur frequently in the natural environment (Cabrol et al, 2003), in airways from individuals with cystic fibrosis (D'Argenio et al, 2007;Smith et al, 2006), in intubated patients (Denervaud et al, 2004) and in individuals suffering from bacteraemia, pneumonia or wound infection (Hamood et al, 1996). This is intriguing, since the LasR regulator is widely considered essential for full P. aeruginosa virulence (Preston et al, 1997;Rumbaugh et al, 1999;Storey et al, 1998).…”
Section: Introductionmentioning
confidence: 99%